Factors Affecting Tocopherol Concentrations in Soybean Seeds - Carrera, Constanza Soledad (2016)
Soybean seeds contain several health-beneficial compounds, including tocopherols, which are used by the nutraceutical and functional food industries. Soybean tocopherol concentrations are, however, highly variable. Large differences observed in tocopherol concentrations among soybean genotypes together with the relatively simple biosynthetic pathway involving few genes support the feasibility of selecting for high-tocopherol soybean. Tocopherol concentrations are also highly influenced by environmental factors and field management. Temperature during seed filling and soil moisture appear to be the main factors affecting tocopherol concentrations; other factors such as soil fertility and solar radiation also affect concentrations and composition. Field management decisions including seeding date, row spacing, irrigation, and fertilization also affect tocopherols. Knowledge of factors affecting soybean tocopherols is essential to develop management strategies that will lead to the production of seeds with consistent target concentrations that will meet the needs of the nutraceutical and functional food industries.